(untitled) (Interdisciplinary Studies Journal, 2025)
Considering the education as a human right and a necessary prerequisite for the exercise of citizenship, this article aims to analyze the contradictions involved in the right to digital technologies in public education, focusing on Rural Schools. To this end, the question is: to what extent is the right to education using digital technologies, already supported by laws, present in rural schools? This research is characterized as exploratory and bibliographic, proposing the analysis of laws, actions, projects and programs that deal with the use of digital technologies in educational processes, as well as data from the Brazilian Institute of Geography and Statistics and the School Census related to the use of digital technologies. The data analysis demonstrates that the concrete reality of Brazilian rural schools is out of step with national laws, as, while the documentation glimpses the advances in Digital Information and Communication Technologies for the decentralization of access to knowledge, the minimum infrastructure to enable the Traditional teaching/learning processes still do not cover all peasant schools. Thus, it can be inferred that education as a human right needs to go beyond laws, to become a concrete reality in all rural schools.